Perceived harmfulness of substance use: A pilot study - Siddharth Sarkar; Srinivas Balachander; Debasish Basu (Wolters Kluwer Medknow Publications, 2014)
Background: Harm ratings of substances help in understanding the perception toward substance use and formulating policies. Evidence of such harm ratings by substance users and their caregivers provides a clearer perspective of those who experience and observe such harm closely. Materials and Methods: Substance users and their caregivers were recruited from the Drug De-addiction and Treatment Centre of PGIMER, Chandigarh. Sociodemographic details of the subjects were noted. The subjects were then asked to rate a list of psychoactive preparations according to the harms they thought the preparation caused. The list of substances was developed taking into consideration substance commonly encountered in the geographical area. The harm ratings were transformed on a scale of 0-100. Results: All subjects were males and majority of them were educated above 10 th standard, were not employed and belonged to urban background. Most of them had taken psychoactive substances in their lifetimes but were currently abstinent. Most of the subjects endorsed intravenous drugs as the most harmful, followed by heroin. Beer and chewable tobacco considered the least harmful substances. Greater degree of education was associated with lower harm rankings for heroin, cannabis, dextropropoxyphene, and raw opium; while urban residence was associated with greater harm ratings for cannabis and raw opium. Differences in the harms were perceived for different preparations of the same active compound for alcohol and nicotine. Conclusion: Harm ratings of substances can be a useful guide while formulating policies and allocating resources. Need for further research extending this pilot study is emphasized.